Hyperbaric oxygen therapy in the treatment of complications of irradiation in laryngeal cancer - Uslu, Gonca Hanedan; Çebi, Gamze; Çobanoğlu, Bengü (Contemporary Oncology/Współczesna Onkologia, 2018)
One of the standard treatments in laryngeal cancer is radiotherapy (RT). Many short- and long-term complications can occur in the region that has received radiotherapy. Definitive treatment of the emerging complications is still debatable, and treatment is challenging for radiation oncologists and ear nose throat specialists. Recently, hyperbaric oxygen treatment (HBOT) has become a promising alternative for the treatment of these complications. The aim of this report is to discuss the effectiveness of HBOT in the treatment of late-term RT-related potential complications in a patient with laryngeal cancer. We applied HBOT for a 58-year-old male patient with laryngeal cancer for the treatment of laryngeal oedema, and dyspnoea that developed one year after RT. In a decompression chamber at 2.4 atm pressure, the patient was made to breath 100% oxygen with a mask for 90 minutes. At the beginning, HBOT was planned for 30 days; however, it was terminated upon improvement of the symptoms at the 19th session. The symptoms, which developed one year after RT, were relieved completely with HBOT, and the patient is maintaining his life without any complaint under our control. The HBOT can be an alternative treatment for late-term complications developed after radiotherapy. It can be especially used for laryngeal oedema, and dyspnoea related to the field of radiotherapy.